Absorbable gelatin plug does not prevent iatrogenic preterm premature rupture of membranes after fetoscopic laser surgery for twin–twin transfusion syndrome. (2nd September 2013) - Papanna, R.; Mann, L. K.; Moise, K. Y.; Johnson, A.; Moise, K. J.
ABSTRACT Objective Despite fetoscopic laser ablation (FLA) having emerged as an effective treatment for twin–twin transfusion syndrome (TTTS), major postintervention challenges, such as iatrogenic preterm premature rupture of membranes (iPPROM), remain. A chorioamniotic plug (CAP) made of absorbable gelatin sponge has been used to seal the trocar entry site in the chorioamniotic layers to promote healing and prevent iPPROM, yet the results have been equivocal. Our objective was to test the hypothesis that, following FLA for TTTS, iPPROM may be prevented by placement of an absorbable gelatin CAP. Methods A retrospective cohort study was performed on prospectively collected data from 134 consecutive patients who underwent FLA for TTTS. The decision for CAP placement was at the discretion of the physician. Preoperative, operative and postoperative variables were collected and analyzed. The primary outcome was the incidence of iPPROM, and the secondary outcomes were procedure‐to‐delivery interval and gestational age at delivery. Comparative statistical analysis was performed as appropriate. Results A CAP was placed in 72 (54%) of 134 patients. Factors significantly associated with CAP placement were higher gravidity (P = 0.03), anterior placentation (P = 0.04), general endotracheal intubation (P = 0.02) and a cannula diameter of 12‐Fr (P = 0.003). There were no differences between CAP and no‐CAP groups in the rate of iPPROM (39% vs 34%, respectively; P = 0.42) or in the procedure‐to‐delivery interval (65.3 ± 34.7 days vs 58.2 ± 30.8 days, respectively; P = 0.21). The gestational age at delivery was later in the CAP group compared with the no‐CAP group (30.7 ± 4.5 weeks vs 28.9 ± 3.9 weeks, respectively; P = 0.02). Conclusions CAP did not reduce the overall risk for iPPROM and did not increase the procedure‐to‐delivery interval. Further research is needed to identify other methods to prevent iPPROM and prolong pregnancy after laser therapy. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.